2022
DOI: 10.1002/emp2.12648
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating properties of occupancy rate and workload to estimate crowding: A Swedish national cross‐sectional study

Abstract: Background Emergency department (ED) crowding causes increased patient morbidity and mortality. ED occupancy rate (OR; patients by treatment beds) is a common measure of crowding, but the comparability of ORs between EDs is unknown. The objective of this investigation was to investigate differences in ORs between EDs using staff‐perceived workload as reference. Methods This was a national cross‐sectional study in Sweden. EDs provided data on census, treatment beds, staf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Although the definition is universal, the extent of the problem and its consequences may vary between institutions, being more prominent in urban and academic EDs (25,26). A recent study by Af Ugglas et al (27) found variable association between crowding and mortality within Sweden and a previous study by our group showed considerable differences in resource availability in Sweden, specifically treatment beds and staffing in relation to patient volume (15). Our study included a mix of rural, urban and academic centers which may contribute to the lack of association between crowding and mortality.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Although the definition is universal, the extent of the problem and its consequences may vary between institutions, being more prominent in urban and academic EDs (25,26). A recent study by Af Ugglas et al (27) found variable association between crowding and mortality within Sweden and a previous study by our group showed considerable differences in resource availability in Sweden, specifically treatment beds and staffing in relation to patient volume (15). Our study included a mix of rural, urban and academic centers which may contribute to the lack of association between crowding and mortality.…”
Section: Discussionmentioning
confidence: 81%
“…There was also a large variation in baseline occupancy rate (Supplementary Table S2). Previous studies from our group and others (15,(28)(29)(30) have shown that crowding may indeed vary between EDs and that scores need to be adjusted to the individual site. In this study, we also found large intra-day variations at all EDs for both mSEAL scores and occupancy rate (Supplementary Tables S2, S3).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This problem persists globally 1 , 6 despite the differences between healthcare policies in different countries 7 , 8 , Sweden being no exception 6 , 9 11 . Previous studies showed a high workload for the main Swedish hospitals 12 , pointing out the multifaced nature of operational errors 11 , 13 , negative patient experience of high waiting times 14 , and the decreasing availability of beds followed by an increasing of patients visiting ED 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This pipeline was designed to analyse a real-world case study that consisted of one year (2019) of hospital production data following patients that visited the Uppsala University Hospital ED. The Uppsala ED constituted an ideal case study because of the reported serious shortcomings and hospital overcrowding in the timespan of the data records 6 , 9 11 .…”
Section: Introductionmentioning
confidence: 99%